EVALUATION THE USING OF PLASTIC SACK RUBBISH AS FABRICS ON EXPANSIVE EMBANKMENT - Agus Setyo Muntohar (Jurnal Semesta Teknika UMY, 2000)
Soil stabilization or soil treatment has been employed and developed time by time. Fabrics are commonly used, especially polypropylene (PP), polyvinyl, or polyethylene. Plastic rubbish is solid waste that comprised by PP. This paper described them as soil reinforcement and their application. The fiber mixtures vary in length that are 5 mm, 10 mm, 20 mm and the content 0.5%, 1% of dry weight. The main equipment for this test is direct shear test (DST). According the test result and discussion, it was shown that the rubbish (plastic sack) has enhanced the shear strength of clay soil. Fiber content 0.5% is better than 1 % to provide shear resistance. The stability of embankment, analyze by Bishop Method with RSS program, increased from 1.458 to be 2.247 at 0.5% fiber content – length 20 mm.